Knowledge assessment of respiratory therapists on endotracheal tube suctioning in intensive care units of public hospitals in Sana’a, Yemen - Abdul Fattah Al-Jaradi; Fares N AL-Wajeeh; Ahmed M AL-Khawlani; Alaa M Al-Jahshari; Aziz M Hisan; Hamza A AL-Gonaid; Alhasan A Seraj; Mohammed H Al-Khawlani; Makram A Mohamed Moqbel; Yahay M Munss; Hamdi A Al-Hamdi; Mohammed A AL-Gohaly (Journal of Mechanical Ventilation)
Background